The bipolar assembly domain of the mitotic motor kinesin-5 - Acar, Seyda (Nature Pub. Group, 2013)
An outstanding unresolved question is how does the mitotic spindle utilize microtubules and mitotic motors to coordinate accurate chromosome segregation during mitosis? This process depends upon the mitotic motor, kinesin-5, whose unique bipolar architecture, with pairs of motor domains lying at opposite ends of a central rod, allows it to crosslink microtubules within the mitotic spindle and to coordinate their relative sliding during spindle assembly, maintenance and elongation. The structural basis of kinesin-5’s bipolarity is, however, unknown, as protein asymmetry has so far precluded its crystallization. Here we use electron microscopy of single molecules of kinesin-5 and its subfragments, combined with hydrodynamic analysis plus mass spectrometry, circular dichroism and site-directed spin label electron paramagnetic resonance spectroscopy, to show how a staggered antiparallel coiled-coil ‘BASS’ (bipolar assembly) domain directs the assembly of four kinesin-5 polypeptides into bipolar minifilaments.